Kaji Eksperimental Cyclone Separator Pada System Pneumatic Conveying Dengan Variasi Partikel Padat - Martinus Rudy Irwanto Sihotang; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Cyclone Separator is a device that uses the principle of centrifugal force and low pressure due to turnaround to separate material based on different types and sizes. The phenomenon of arising in the cyclone separator installed in suction or press: collection efficiency decline marked by the large number of dust particles is wasted/fluttering giving rise to pollution of the surrounding area of the factory, the pressure drop It may cause loss of energy. This problem can affect the results and costs of production. This research aims to know the characteristics of the incoming velocity and mass flow rate of dust particles towards efficiency and a decrease in the pressure of the cyclone suction and press. By selecting the test type cyclone dust types vary the swift, the inflow velocity and mass flow rate of the cyclone dust. Testing takes place at room temperature. The test results provide that increased pressure drop in the inflow velocity and mass flow rate of the dust increases. Cyclone efficiency is increased when the density (mass flow rate of the increase in dust) and high flow cyclone mounted on suction position. On the contrary position press the efficiency decreases at a speed the flow of incoming cyclones enlarged. So the cyclone separator mounted suction more profitable than farmed ingredients press.KeyWords: Cyclone Separator, Particulate Matter, Efficiency Cyclone